Development and Validation of a Creativity Assessment Rubric for Evaluating Student Projects in Higher Education - Vita Amanda; Sophia Lucille Rodriguez (Enigma in Education, 2026)
Educators in higher education lack psychometrically validated instruments for assessing student creative output, despite creativity being recognized as a core 21st-century competency. This study aimed to develop and validate the Creative Output Assessment Rubric (COAR) for evaluating student creative projects in university settings. A multi-phase instrument development design was employed at a private university in Palembang, Indonesia, during the 2023/2024 academic year, comprising item generation and expert review (n = 8; S-CVI/Ave = 0.92), pilot testing (n = 45), exploratory factor analysis (n = 215), and confirmatory factor analysis with an independent sample (n = 220). A five-factor structure—Originality, Elaboration, Flexibility, Aesthetic Quality, and Technical Execution—comprising 22 items was confirmed, explaining 67.4% of total variance. The confirmatory model demonstrated good fit (CFI = 0.94; TLI = 0.93; RMSEA = 0.048). Internal consistency was strong (Cronbach's α = 0.93; McDonald's ω = 0.94), inter-rater reliability was adequate (ICC = 0.84; 95% CI: 0.79–0.88), and criterion validity was supported by a significant correlation with independent expert ratings (r = 0.74; p < 0.001). Configural measurement invariance held across four academic faculties. The COAR is a valid and reliable instrument for assessing student creative output in higher education, offering educators a validated scoring framework for the formative and summative evaluation of creative work across academic disciplines.